Management, vol. 22 (2018) - Moczulska, Marta - red.; Preston, Peter- red. jęz.; Stankiewicz, Janina - red. nacz.; Zmyślony, Roman - red. statyst.; Adamczyk, Janusz- red.; Skalik, Jan - red. (Zielona Góra: Faculty of Economics and Management Press)
The periodical "Management" is aimedat publishing original, empirical and theoretical studies, short communications and preliminary reports on modern management. Emphasis is laid on investigations in strategic management. The journal also intends to give an insight into the computer-related aspects of management, integrated and manufacturing systems, information systems, robotics and other related fields.
Keywords: Zarządzanie przedsiębiorstwem; ekonomia